2012
DOI: 10.1097/dad.0b013e31823931b4
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and KRAS Mutations in Sporadic Glomus Tumors

Abstract: Glomus tumors are rare soft tissue neoplasms resembling the normal glomus body, which is a specialized form of arteriovenous anastomosis that regulates heat. The molecular genetics of sporadic glomus tumors has not been studied. We genotyped tumors from 28 patients (16 female patients and 12 male patients) ranging from 13 to 77 years and correlated the results with the tumor site (15 finger/1 hand/4 arm/7 leg/1 eyelid), Ki-67 index, and clinical follow-up. Tumor DNA from paraffin-embedded tissue was screened b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Furthermore, an association between digital glomus tumor and neurofibromatosis has been reported, with a biallelic inactivation of NF1 proposed as the mechanism of glomus tumor formation in this setting (Brems et al, 2009). A small rate of BRAF and KRAS mutations have been detected in sporadic soft tissue GT, which appears to be within the expected range of mutations described in other tumor types (Chakrapani et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, an association between digital glomus tumor and neurofibromatosis has been reported, with a biallelic inactivation of NF1 proposed as the mechanism of glomus tumor formation in this setting (Brems et al, 2009). A small rate of BRAF and KRAS mutations have been detected in sporadic soft tissue GT, which appears to be within the expected range of mutations described in other tumor types (Chakrapani et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on glomus tumor, by contrast, showed a lack of b-catenin nuclear expression and CTNNB1 activating mutations. 19,28 Therefore, nuclear b-catenin expression and the presence of CTNNB1 mutations can be useful in distinguishing glomangiopericytoma and glomus tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Glomus tumours may be associated with neurofibromatosis-1, 41,42 and a subset of sporadic cases have been associated with BRAF (V600E) or KRAS (G12A) mutations. 43 After publication of the WHO classification, NOTCH mutations (of either NOTCH2 or NOTCH3) have also been demonstrated to be present in some glomus tumours. 44 …”
Section: Pericytic (Perivascular) Tumoursmentioning
confidence: 97%